Erythropoietin does not affect TNF and IL-6 production directly. - Cervellini, I; Sacre, S; Ghezzi, P; Mengozzi, M (2013)
The tissue-protective action of erythropoietin (EPO) in animal models is often associated with reduced inflammation. However, there are many contrasting reports of the effect of EPO on the production of inflammatory cytokines induced by lipopolysaccharide (LPS) in vitro, with different papers reporting an inhibition, an upregulation, or a lack of effect. Negative results are likely underestimated by a publication bias. As EPO has anti-inflammatory actions in models associated with tissue injury, we hypothesized that EPO could specifically inhibit the induction of inflammatory cytokines by danger signals associated with cell death, and investigated its effect on the induction of IL-6 or TNF by high-mobility group-box 1 protein (HMGB1) or by necrotic cells. We did not observe any significant effect of EPO in these models; neither EPO affected the response induced by TLR agonists different from LPS, or by extracellular ATP-mediated activation of the inflammasome. We conclude that the inhibition of inflammation by EPO is likely to be an indirect effect, secondary to its tissue-protective activity, or that it requires a prior priming induced by the injury.